Adaptive threshold scheme for fault detection for positive switched systems with parametric uncertainty - Kenza Telbissi (E3S Web of Conferences)
This paper addresses the challenge of designing a fault detection observer for actuators and sensors in a particular class of positive switched systems, using the average dwell time method. The proposed approach involves the concurrent generation of residuals and a dynamic threshold, enhancing the precision and efficiency of fault detection. Additionally, our work introduces an innovative method for fault detection with parametric uncertainties, outlining sufficient conditions for designing the observer using Linear Programs (LP). The effectiveness of the proposed approach is validated through a numerical simulation.